Liposomal formulation of curcumin attenuates seizures in different experimental models of epilepsy in mice. (2nd November 2011) - Agarwal, Nidhi Bharal; Jain, Seema; Nagpal, Dheeraj; Agarwal, Nitin Kumar; Mediratta, Pramod K.; Sharma, Krishna K.
Abstract Contemporary research indicates promising anticonvulsant effect of curcumin. However, its poor oral bioavailability is a major hindrance toward its pharmacological action. Thus, this study was carried out to evaluate the acute effect of liposome‐entrapped curcumin on increasing current electroshock seizures (ICES) test, pentylenetetrazole (PTZ)‐induced seizures, and status epilepticus in mice. Liposome‐entrapped curcumin in doses 25 and 50 mg/kg demonstrated significant increase in seizure threshold current and latency to myoclonic and generalized seizures in ICES test and PTZ‐induced seizures, respectively. Similarly, liposomal‐entrapped curcumin also increased the latency to the onset and decreased the duration of seizures during status epilepticus in mice. To conclude, liposomal‐entrapped curcumin possesses anticonvulsant activity against status epilepticus in mice.